The secret of the old clock - Keene, Carolyn (New York : Grosset & Dunlap, 1987)
Nancy Drew's keen mind is tested when she searches for a missing will.
Rescue -- Missing will -- Unpleasant meeting -- Racing the storm -- Surprising story - Exciting appointment -- Angry dog -- Forgotten secret - Helpful disclosures -- Following a clue -- Unexpected adventure -- Desperate situation -- Frustrating wait -- Tense chase -- Nancy's risky undertaking -- Capture -- Strange instructions -- Suspenseful search -- Startling revelations -- Happy finale.
Keywords: Drew, Nancy (Fictitious character) -- Juvenile fiction; Mystery and detective stories